Construction of Sexual and Gender Minority Identity among Malay-Muslim Natal Females: A Meta-Synthesis - Syed Jaapar, Sharifah Zubaidiah; Muhamad, Rosediani; Abdul Razak, Asrenee; Bakar, Mujahid (IIUM Medical Journal Malaysia, 2023)
Malay-Muslim identity is the regular norm among Malays in Malaysia; however, this identity has been challenged with the emergence of sexual-and-gender minority (SGM). Even though Malay cultural values and Islamic teachings prohibit same-sex orientation and cross-gender, a SGM group has evolved among Malay-Muslim natal females. This meta-synthesis was conducted to explore the psychosocial factors involved in the construction of SGM and its consequences among Malay natal females in Malaysia using the Sandelowski-Barroso approach. A systematic search of articles was done in the selected databases by using identified keywords between October to December 2020. Twelve full articles were included after proper screening and in-depth reviews. The quality of these articles was assessed independently by two researchers. The articles were then analysed using ATLAS.ti 8 software to group the data into subthemes and themes. Lastly, the effect sizes of each subtheme were calculated. Three main themes were identified: affection seeking, hurtful experience and nurturing influences. Malay natal females also shared consequences following construction of SGM identity which include acceptance from community, continuous conflicts in life and mental health consequences. This meta-synthesis revealed the influences that shape the construction of Malay SGM women. Thus, interventions shall be planned to aid them according to cultural and psychosocial factors.